Incidence of pressure injuries in fracture patients: A systematic review and meta-analysis. Issue 4 (November 2022) - Jiao, Yanxia; Yuan, Chenlu; Wu, Tong; Zhang, Hongyan; Wei, Yuting; Ma, Yuxia; Zhang, Xiujuan; Han, Lin
Abstract: Objective: To systematically evaluate the incidence of pressure injuries (PIs) in hospitalized fracture patients and to provide evidence for the prevention and treatment of PIs. Methods: A systematic review and meta-analysis was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. Electronic databases including PubMed, Embase, the Cochrane Library, Web of Science, CINAHL, China Knowledge Resource Integrated Database (CNKI), WanFang Database, Weipu Database (VIP), and Chinese Biomedical Database (CBM) were searched to collect cross-sectional studies and cohort studies related to PIs among hospitalized fracture patients. All electronic literature sources were searched from inception to March 2022, and a hand-search through references was also conducted to find relevant articles. Studies were evaluated independently by two researchers and audited by a third researcher. The data were extracted and presented in tables. The risk of bias was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. All data analysis used Stata14.0. The I 2 statistic and random-effects model were used to determine the heterogeneity. Results: A total of 7906 articles were screened, and 18 studies with 8956 patients were ultimately involved in this review. The pooled incidence of PIs in the fracture patients was 20.4% (95% CI : 14.9 to 25.8), and the incidence of PIs only in spinal and hip fracture patients was 23.9% (95% CI : 19.6 to 28.2). The incidence of PIs in 65 years old or over was significantly high (23.3% [95% CI : 15.3 to 31.2]). The most affected body sites were sacrococcygeal regions (56.7%) and heels (19.9%). The most common stages were stage 2 (62.2%) and stage 1 (17.4%). Conclusion: The overall incidence of PIs in fracture patients was as high as 20.4%, significantly higher than the average incidence of adults. We found that the potential for PIs in fracture patients increases with age. Hence, our discoveries recommended that healthcare givers should consider reducing the occurrence of PIs. Additionally, more research may be conducted to improve the understanding of characteristics of PIs among fracture patients and to identify PIs risk factors to prevent and treat them effectively. Highlights: Conducted a systematic review and meta-analysis to analyze the incidence of fracture patients. Analyzed the most frequent body sites and stages of pressure injury for fracture patients. Compared the incidence of pressure injuries by age and by fracture type. Explored the risk factors which affected pressure injuries for elderly fracture patients.